An Analytical Data Management as a Cloud Service for Numerical Simulations - Costa, Ramon G.; Porto, Fábio; Schulze, Bruno (Anais do Brazilian e-Science Workshop (BreSci), 2012)
Numerical simulation of natural phenomena is being fostered by recent advances in powerful high processing computing platforms. Scientists in various areas, such as human cardiovascular system, model a phenomenon being studied through a set of mathematical equations. The latter are transformed into a computing model, using one of the available numerical methods. As scientists strive to obtain a more realistic simulation, a huge amount of data is produced. Unfortunately, there has been little work on supporting numerical simulation data management, which leaves simulation scientists with huge standard text files and complex analytical programs that eventually extract some meaningful information to validate scientific hypotheses. In this context, this paper tries to bridge this gap by raising some issues involved in numerical simulation data analysis. A representation for numerical simulation data is presented that considers a multidimensional model, for dimensional variables, and their corresponding physical quantities. An initial set of analytical operators are identified and their semantics discussed. The SciDB system is used to implement a first prototype supporting the human cardiovascular system simulation developed at the LNCC. Additionally, a cloud service to interface with the numerical simulation data manager is proposed and its integration with the Neblina cloud middleware is explored. We expect that this work will provide a better understanding concerning the needs involved in analytical data management for multidimensional numerical simulations.